Assembly and Installation of SDP Lighting Panels: Assembly dan Instalasi Panel SDP Lighting - Rohman, Rizky Habibur; Anshory, Izza (Procedia of Engineering and Life Science, 2024)
Electrical panels have an important role in distributing electrical energy and securing it. One type of electrical panel that is often used is the SDP Panel (Sub Distribution Panel), especially in the context of lighting. This article discusses the assembly and installation process of SDP Lighting Panels, which have a crucial role in maintaining the availability, efficiency and safety of lighting systems. The SDP Panel assembly process involves preparing components such as MCB (Miniature Circuit Breaker), MCCB (Moulded Case Circuit Breaker), Fuse , ELCB (Earth Leakage Circuit Breaker), and other components. After that, these components are carefully assembled according to the previously prepared design. Next, SDP Panel installation involves installing the panels to a location according to the plan and connecting them to the building's main power system. Accurate wiring and thorough testing are necessary to ensure that the panels function properly. It is important to understand that SDP Lighting Panel installations must comply with applicable electrical safety regulations and standards to avoid the risk of fire, electrical disturbances or injury. Errors in the installation or assembly process can have a negative impact on the lighting system and safety. Therefore, a good understanding of the SDP Lighting Panel assembly and installation process is very important to ensure a reliable, efficient and safe lighting system